Inter‐individual variation of bolus properties in triggering swallowing during chewing in healthy humans. (25th July 2020) - Maeda, Rumiko; Takei, Eri; Ito, Kayoko; Magara, Jin; Tsujimura, Takanori; Inoue, Makoto
Abstract: Background: There is a wide variation of chewing behaviours even in healthy humans. The present study was aimed to clarify how the rheological properties of the bolus during chewing are different among individuals. We also investigated whether the swallowing threshold was consistent among the individuals and whether the difference in the bolus properties at the swallowing affected swallowing movement. Methods: Twenty‐nine healthy volunteers were asked to ingest 8 g of steamed rice. Based on the chewing duration defined by the time until first swallow, participants were asked to chew the food and then either spit it out or swallow it at 50%, 100% and 150% of chewing duration. In seven volunteers, the maximum bite force was measured. Results: The hardness of the bolus gradually decreased throughout recording. Although the chewing duration varied widely, there was a significant negative correlation between time and hardness, regardless of the difference in individual chewing duration. The cohesiveness of the bolus was unchanged at the 100% time point, followed by a slight but significant increase. There was no significant correlation between the chewing duration and adhesiveness of the bolus. Swallowing‐related bursts of Supra and Infra EMGs were not related to the chewing duration or bolus properties, and chewing duration did not affect swallowing function. Conclusion: The current results suggest that the bolus properties such as the hardness and cohesiveness during chewing are just dependent on the chewing duration and the difference in the bolus properties does not affect the swallowing initiation and movement.